FUTURE-PROOFING VOCATIONAL EDUCATION: THE EMERGENCE OF DIGITAL TOURISM IN UZBEKISTAN - Bozorova Laziza Ilhom qizi (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Annotation: This article explores the future of vocational education in Uzbekistan in light of the emerging digital tourism industry. It examines the challenges and an opportunity presented by the digital transformation of tourism and discusses how vocational education can adapt to meet the changing needs of the industry. The article also highlights the importance of collaboration between government, industry, and educational institutions in ensuring that vocational education programs are aligned with the demands of the digital tourism market.